Intercultural trust. An experiment in Austria and Japan - Robert Jiro Netzer; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2009)
We show that the level of trust and reciprocity in an intercultural trust game experiment between Austrian and Japanese subjects differs from the results of an intracultural experiment run in the respective countries among compatriots. Austrian subjects show significantly higher levels of trust towards Japanese subjects than towards fellow countrymen. Japanese do not differentiate between Austrian or Japanese subjects. Japanese subjects are found to be less reciprocal than Austrian subjects. A post-experimental survey reveals differences in culture-specific dispositions between the two countries that can explain the country-specific differences.
Keywords: C91; C71; 330; intercultural experiment; intracultural experiment; trust game; Austria; Japan; Vertrauen; Kooperatives Spiel; Kulturelle Identität; Österreich; Japan